Economic Benefits and Adoption of Orange-Fleshed Sweetpotato Production Enterprise among Farmers - Udemezue, J. C. (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2021)
The income generation and employment status of root and tuber crops in Nigeria today are not a paradox per say but a reality that secured about 50% jobs for the majority of youths in the rural areas. Orange-fleshed sweetpotato (OFSP) varieties have the complimentary capacity to diversify Nigerian economy into multiple facet one for nation building. Therefore, they are the entry points for development through income and employment generation as well as poverty reduction. In rural area like Nigeria, most households cannot afford food products rich in Vitamin A and this gave rise to the introduction of biofortified agricultural products such as OFSP varieties (OFSVs). OFSP is an improved breed of sweetpotato (Ipomoea batatas [L.] Lam.) that can be cultivated in tropical and semi-tropical regions of the world for food and source of income, especially among the rural dwellers. Vitamin A deficiency is a major risk factor for children, pregnant and lactating women and can even lead to premature death as well as untimely blindness if care is not taken. In the light of this, this paper used analytical approach to review the following; potentials of OFSP variety, OFSVs in Africa, tips for marketing and popularizing OFSP, determinants, and levels of adoption of OFSP production in Nigeria and Ghana.